PENERAPAN METODE ITERATIVE DICHOTOMIZER 3 (ID 3) UNTUK MENENTUKAN BEASISWA BERPRESTASI PADA SMP PGRI CARINGIN SUKABUMI - Saputra, Rizal Amegia; Ramdhani, Lis Saumi; Supriatman, Supriatman (LPPM Universitas Nusa Mandiri, 2019)
Scholarships are assistance from the government to students / students who are less able or have the ability in the academic and non-academic fields that are given individually to reduce the burden in terms of material. Frequently stalling time in selection, the number of students who apply for scholarships, the number of students whose homes are far from school, the number of students who race to come early as one of the criteria eligible to receive scholarships as well as the most scholarship applicants feel disadvantaged by unfavorable decisions. Iterative Dichotomizer 3 (ID3) algorithm is the most basic decision tree learning algorithm (decision tree learning algorithm). This algorithm conducts a thorough search on all possible decisions. In this research, it will be analyzed the application of the iterative dichotomizer 3 method in the case of determining achievement scholarships. In order to make decisions quickly and accurately. From 708 scholarship candidates including 28 eligible and 680 scholarship recipients, 136 scholarship recipients were obtained from ID3 algorithm with 3 eligible and 133 who had not, and obtained an accuracy rate of 97.75% so that it could be concluded that good and can help the school.